From River to Classroom: Integrating Local Culture and Ethno-Pedagogy in Multicultural Education - Arofah, Lumban (Dinasti Publisher, 2025)
This article aims to introduce multicultural education with a stronger emphasis on the context of ethnopedagogy. The newly implemented “Kurikulum Merdeka” enables teachers with greater opportunities to develop learning models and mechanisms that are better suited to their students’ needs. One of the paradigms that enables teachers to design educational models rooted in the local context is ethnopedagogy. This article seeks to illustrate how multicultural education can be implemented through and beyond the framework of ethnopedagogy.